Working Paper 37: The Green Corruption paradox: Natural resource management and environmental corruption in Indonesia (Basel Institute on Governance Working Papers, 2021)
This Working Paper details the findings of a survey of Indonesians’ perceptions of corruption, the economy and the environment in July 2021.The survey was a joint initiative of the Green Corruption team at the Basel Institute on Governance and leading Indonesian pollster Lembaga Survei Indonesia (LSI). It consisted of a national public opinion survey covering 2,580 respondents and in-depth interviews with 30 private-sector representatives working in various natural resource sectors.The survey reveals what we call the Green Corruption paradox: Conflicting, and arguably mutually exclusive, views on all three topics can co-exist. Despite seeing the presence of and being deeply concerned about corruption and environmental degradation, people tend to focus on livelihoods when times are hard. People also, according to the survey data, favour economic structures that appear to channel the benefits of natural resource utilisation more directly to citizens. In Indonesia, this means rejecting private companies – particularly foreign-owned – in favour of state-owned enterprises (SOEs) and people’s cooperatives.The report ends with five key recommendations that can inform Indonesian policy and the interventions of donors and civil society organisations concerned with conservation, anti-corruption and sustainable development.This research was made possible with the generous support of the American people through the USAID CEGAH programme.